Banished from the City: The Exilic Ecclesiology of Luke-Acts - Jeong, Mark (Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe, 2025)
Mark Jeong examines scenes in the New Testament book of Acts where members of the church are banished or exiled from cities. He argues that the author of Luke-Acts presents the church as a community of political exiles, whose exilic way of life is presented as part of following Jesus.